Augmented Reality and Virtual Reality: Transforming Digital Experiences - Dwi Atmodjo WP; Ahmad Syamsudin; Legito; Agustinus Lambertus Suban (Technologia Journal, 2025)
This article discusses the development of Augmented Reality (AR) and Virtual Reality (VR) technologies and their role in the transformation of digital experiences. Using a literature study approach, this study examines various written sources, including scientific journals, technology articles, and recent industry reports, to understand how AR and VR have developed, are applied in various fields, and the challenges faced in their development. The analysis is carried out by comparing the main characteristics of AR and VR, especially in terms of immersion, interactivity, and hardware requirements. The results of the study show that AR is increasingly used in mobile applications, education, manufacturing, and marketing by combining digital elements into the real world. Meanwhile, VR offers a more immersive virtual environment and is widely applied in the entertainment industry, simulation training, and health. Advances in hardware, graphics, and artificial intelligence (AI) have increased the realism and interactivity of these two technologies, expanding their application in various sectors. Although promising, AR and VR still face challenges such as hardware limitations, high production costs, and ergonomic and privacy issues. With continued innovation, AR and VR are expected to be increasingly integrated into various aspects of life, making them key elements in future digital transformation.